Postural stability and pain in obese ladies with mild knee osteoarthritis after intra-articular hyalgan injection - Khalaj, N.; Abu Osman, Noor Azuan; Mokhtar, A.H.; Wan Abas, W.A.B. (Elsevier, 2014)
Purpose: Knee osteoarthritis is a common cause of disability which influences the quality of life. It is associated with pain and impaired knee joint proprioception which effects postural stability. Postural stability is critical for mobility and physical activities. Current treatments for knee OA are analgesics or nonsteroidal anti-inflammatory drugs (NSAIDs), surgical treatments, intra-articular injections, physiotherapy, weight reduction, exercise, orthotic (braces), and patient education. Hyaluronic acid (HA) injection is a nonsurgical new popular treatment used worldwide.